Local corneal UVA crosslinking used for corneal ulcer treatment in a child. A clinical case - I. R. Mamakaeva; A. V. Pleskova; E. N. Iomdina; L. A. Katargina (Российский офтальмологический журнал, 2022)
Purpose: to evaluate the results of corneal ultraviolet (UVA) crosslinking used in the complex treatment of recurrent corneal ulcer in a child. Patient K., 6, was treated in the department of children eye pathology with the diagnosis of corneal ulcer. The case history said the patient was sick for 2 years, periods of remission alternated with exacerbation. Immunological examination revealed sensitization to herpes simplex virus types 1 and 2 (IgG = 3.2 with the norm of < 0.18). The combined treatment included drug therapy and local UVA crosslinking of the cornea (7 procedures per 6 minutes every other day). Optical coherence tomography showed positive changes during treatment: the depth and area of cornea infiltrate became smaller. 1 month after the last procedure, the inflammatory process was stopped and the corneal clarity gradually restored whilst vascular activity became less intense. After 2 months, the infiltrate area became clear throughout. OCT revealed a gradual decrease of the infiltrate thickness and a replacement of the cornea with a transparent tissue.Conclusion. Local corneal UV-crosslinking used as part of the complex treatment of keratitis and corneal ulcers in children is a very promising method for implementation in clinical practice.